Biosynthesis of Gold Nanoparticles by Vascular Cells in vitro - Kitching, Michael; Inguva, Saikumar; Ramani, Meghana; Gao, Yina; Marsili, Enrico; Cahill, Paul (Frontiers in Microbiology, 2022)
Biosynthesis of gold nanoparticles (AuNPs) for antimicrobial and chemotherapeutic applications is a well-established process in microbial hosts such as bacterial, fungi, and plants. However, reports on AuNPs biosynthesis in mammalian cells are scarce. In this study, bovine aortic endothelial cells (BAECs) and bovine aortic smooth muscle cells (BASMCs) were examined for their ability to synthesize AuNPs in vitro. Cell culture conditions such as buffer selection, serum concentration, and HAuCl4 concentration were optimized before the biosynthesized AuNPs were characterized through visible spectrometry, transmission electron microscopy, X-ray diffraction, and Fourier transform infrared (FTIR) spectroscopy. BAECs and BASMC produced small, spherical AuNPs that are semi-crystalline with a similar diameter (23 ± 2 nm and 23 ± 4 nm). Hydrogen peroxide pretreatment increased AuNPs synthesis, suggesting that antioxidant enzymes may reduce Au3+ ions as seen in microbial cells. However, buthionine sulfoximine inhibition of glutathione synthesis, a key regulator of oxidative stress, failed to affect AuNPs generation. Taken together, these results show that under the right synthesis conditions, non-tumor cell lines can produce detectable concentrations of AuNPs in vitro.